2019
DOI: 10.5194/bg-16-2467-2019
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker evidence for the occurrence of anaerobic ammonium oxidation in the eastern Mediterranean Sea during Quaternary and Pliocene sapropel formation

Abstract: Abstract. The eastern Mediterranean Sea sedimentary record is characterised by intervals of organic-rich sapropel sediments, indicating periods of severe anoxia triggered by astronomical forcing. It has been hypothesised that nitrogen fixation was crucial in injecting the Mediterranean Sea with bioavailable nitrogen (N) during sapropel events. However, the evolution of the N biogeochemical cycle of sapropels is poorly understood. For example, the role of the complementary removal reactions like anaerobic ammon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 57 publications
1
45
0
Order By: Relevance
“…This hypoxia influences the microbial community structures (Gillies et al, 2015;Gillies Campbell et al, 2019) and BHP assemblages have been shown to vary with redox conditions elsewhere (Wakeham et al, 2007;Sáenz et al, 2011b;Kharbush et al, 2013;Ricci et al, 2014;Rush et al, 2014;Höfle et al, 2015;Matys et al, 2017). BHT II accumulates under suboxic and anoxic conditions (Sáenz et al, 2011b;Matys et al, 2017) and, more recently, it has been used as a proxy for anammox bacteria when present in high abundance relative to BHT [BHT II ratios; BHT II/(BHT + BHT II)] (Rush et al, 2014(Rush et al, , 2019Matys et al, 2017). Support for an anammox origin of BHT II comes from its significantly δ 13 C-depleted values (-50.6%) in a Mediterranean Sea sediment (Hemingway et al, 2018).…”
Section: Diagenetic and Redox Influence On Bhp Distributionsmentioning
confidence: 99%
“…This hypoxia influences the microbial community structures (Gillies et al, 2015;Gillies Campbell et al, 2019) and BHP assemblages have been shown to vary with redox conditions elsewhere (Wakeham et al, 2007;Sáenz et al, 2011b;Kharbush et al, 2013;Ricci et al, 2014;Rush et al, 2014;Höfle et al, 2015;Matys et al, 2017). BHT II accumulates under suboxic and anoxic conditions (Sáenz et al, 2011b;Matys et al, 2017) and, more recently, it has been used as a proxy for anammox bacteria when present in high abundance relative to BHT [BHT II ratios; BHT II/(BHT + BHT II)] (Rush et al, 2014(Rush et al, , 2019Matys et al, 2017). Support for an anammox origin of BHT II comes from its significantly δ 13 C-depleted values (-50.6%) in a Mediterranean Sea sediment (Hemingway et al, 2018).…”
Section: Diagenetic and Redox Influence On Bhp Distributionsmentioning
confidence: 99%
“…Here, we investigated the δ 13 C value of sedimentary organic matter of surface sediments deposited within the OMZ of the Arabian Sea and employed a simple isotope mixing model to investigate the extent of input from OMZ carbon fixation into sedimentary organic matter. As the major process in the Arabian Sea OMZ 10.1029/2019GB006282 Global Biogeochemical Cycles known to produce isotopically light biomass is anaerobic oxidation of ammonia (anammox; Ulloa et al, 2012;Villanueva et al, 2014), in order to determine the isotopic signature of this pathway, we developed and applied a method to determine the δ 13 C values of a novel biomarker, bacteriohopanetetrol stereoisomer (BHT'), which has been found to be unique to anammox bacteria in the marine environment in culture and environmental studies (Rush et al, 2014(Rush et al, , 2019Rush & Sinninghe Damsté, 2017). It has been found in the Arabian Sea and other marine anoxic settings (Matys et al, 2017;Sáenz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Core and intact archaeal isoprenoidal GDGTs can be now analyzed in a single run using reversed-phase chromatography (Zhu et al, 2013), while the analysis of core bacterial and archaeal GDGTs has been improved by the use of ethylene bridged hybrid (BEH) HILIC columns (Hopmans et al, 2016). The detection of BHPs has been improved by the analysis of non-derivatized compounds using either atmospheric pressure chemical ionization (APCI) (Talbot et al, 2016) or electrospray ionization (ESI) (Rush et al, 2019).…”
Section: Chromatographymentioning
confidence: 99%